2008
DOI: 10.1007/s10832-007-9400-3
|View full text |Cite
|
Sign up to set email alerts
|

Annealing temperature effect on ferroelectric and magnetic properties in Mn-added polycrystalline BiFeO3 films

Abstract: We fabricated 5 at.% Mn-added polycrystalline BiFeO 3 films and investigated the annealing temperature effect on structural, ferroelectric and magnetic properties. In the x-ray diffraction patterns, only the diffraction peaks due to the BiFeO 3 structure were observed and no secondary phase could be observed at annealing temperatures between 773 and 923 K. Adding Mn suppressed the leakage current density in the high electric field region when compared to pure BiFeO 3 films. The conduction mechanism of the Mn-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“…and volatilization of Bi [12]. In general, the concentration of oxygen vacancy in BFO thin films increases with the rise of annealing temperature so that the leakage current increases [37,38]. It is not consistent with our results.…”
Section: Resultscontrasting
confidence: 81%
“…and volatilization of Bi [12]. In general, the concentration of oxygen vacancy in BFO thin films increases with the rise of annealing temperature so that the leakage current increases [37,38]. It is not consistent with our results.…”
Section: Resultscontrasting
confidence: 81%
“…Many studies attempted to decrease the leakage current in BiFeO 3 films by adding appropriate additives and refining the preparation conditions. [1][2][3][4][5] It is useful to know the J-E properties of such leaky specimens in a high electric field region for investigating the conduction mechanism and obtaining the guidelines to reduce the leakage current.…”
mentioning
confidence: 99%
“…Amongst the several multiferroic materials, BiFeO 3 (BFO) is probably the only lead-free multiferroic material showing room temperature ferroelectric and G-type anti-ferromagnetic orders simultaneously. Rhombohedrally distorted perovskite (ABO 3 ) structured BFO, with R3c space group shows high anti-ferromagnetic Neel temperature, (T N ~ 370 °C) and high ferroelectric temperature (T C ~ 830 °C) [5,6]. The anti-ferromagnetic nature in BFO arises due to partially filled d-orbitals of Fe 3+ at B site, and ferroelectric order develops due to the presence of 6s 2 lone pair of electrons of Bi 3+ at A site [7].…”
Section: Introductionmentioning
confidence: 99%
“…Chandel et al reported enhanced electrical and magnetic properties in Mn-doped BFO nanoparticles [22]. Hiroshi et al investigated the impact of annealing temperature on Mn-doped BFO films [6]. The effect of Mn-doping concentration on the multiferroicity of BFO was investigated by Chauhan et al [5].…”
Section: Introductionmentioning
confidence: 99%